Mindfulness Sebagai Terapi yang Efektif untuk Meningkatkan Kualitas Hidup Pasien dengan Coronary Artery Disease - Silaban, Anna Ria; Nurachmah, Elly; Yona, Sri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
There are various risk factors for coronary heart disease, one of which is psychological factors, such as: stress, anxiety, depression to loneliness; which can affect the patient's quality of life and life satisfaction. One therapy that can equip patients with the ability to overcome these problems is mindfulness. This study aimed to determine the effectiveness of mindfulness therapy to improve the quality of life of patients with coronary artery disease. This study was a systematic review with the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" approach. Literature search based on online databases, such as: ProQuest, ClinicalKeys, Science Direct, and Oxford Journals published from 2018 to 2024 and the articles used were assessed using the JBI Critical Appraisal Tools. In this study, 10 articles were obtained for review. The results of the review showed that mindfulness was effective in improving quality of life (2 articles), increasing psychological stability (6 articles) and controlling and preventing heart risk factors (2 articles). Based on these results, it could be concluded that mindfulness is an effective therapy to improve quality of life, increase psychological stability and control and prevent heart risk factors in patients with coronary artery diseaseKeywords: coronary artery disease; mindfulness; therapy; quality of life ABSTRAK Ada berbagai faktor risko penyakit jantung koroner, salah satunya adalah faktor psikologis, seperti: stres, kecemasan, depresi hingga loneliness; yang dapat memengaruhi kualitas hidup pasien dan kepuasan hidupnya. Salah satu terapi yang dapat membekali pasien dengan kemampuan untuk mengatasi masalah tersebut adalah mindfulness. Studi ini bertujuan untuk mengetahui efektivitas terapi mindfulness untuk meningkatkan kualitas hidup pasien dengan coronary artery disease. Studi ini merupakan systematic review dengan pendekatan “Preferred Reporting Items for Systematic Reviews and Meta-Analyses”. Pencarian literatur berdasarkan online database, seperti: ProQuest, ClinicalKeys, Science Direct, dan Oxford Journals yang terbit dari tahun 2018 sampai 2024 dan artikel yang digunakan dinilai dengan JBI Critical Appraisal Tools. Pada studi ini didapatkan 10 artikel untuk ditinjau. Hasil review menunjukkan bahwa minfulness efektif untuk meningkatkan kualitas hidup (2 artikel), meningkatkan stabilitas psikologis (6 artikel) dan mengendalikan serta mencegah faktor resiko jantung (2 artikel). Berdasarkan hasil tersebut dapat didimpulkan bahwa mindfulness merupakan terapi yang efektif untuk meningkatkan kualitas hidup, meningkatkan stabilitas psikologis serta mengendalikan dan mencegah faktor risiko jantung pada pasien dengan coronary artery diseaseKata kunci: coronary arteri disease; mindfulness; terapi; kualitas hidup